Pertanggungjawaban Agen Asuransi Terhadap Perusahaan Asuransi Jika Tertanggung Melakukan Wanprestasi - Eki Dyata Fredi Setiawan, Herman Susetyo*), Hendro Saptono (Diponegoro Law Journal, 2013)
Insurance agents is a frontliner in the insurance business, because they have an important role in helping insurance companies to market and sell insurance products, even to the closing of the insurance. Basically the relationship between an insurance agent and the insurance company is a delegation of authority, because the insurance company as the principal authorized the insurance agent to do his duties on behalf of the insurance company and the insurance agent relationships with insurance companiesis a not fixed relationship. Someone who wants to become an insurance agent should complete the requirements such as a license or certificate and have to attend training sessions held by the insurance company. Insurance agent and the insurance company tied to an agency agreement, which is contain the rights and obligations, responsibilities of insurance agents and also insurance agents code of ethics. All contents of the agency agreement must be fulfilled and executed by both parties to create a harmonious relationship of insurance business.In particular, this study aimed to: Seeing the legal relationship between the parties i.e. the insurance company, insurance agent and the insured as well as the implementation of the rights and obligations of the parties under the agency agreement and the legal responsibilities of each party involved in the insurance.Method research approach used is the normative juridical literature, with research through the study of literature (library research) and also called as a study document (documentary research), the main material used in the study is the data or documents as well as a Primary Data or Secondary Data. At the research, the authors analized the agency agreements, insurance policies and other documents that support the insurance business.Based on the description above, it can be concluded that: agency agreements, insurance policies and other documents that support the insurance process is as it should be and it protects the parties, if there is an agencies who do not fullfilled the duties that have been provided in the agreement on the agency agreement, it would breaking the agreement and the agreement will be expired. Liability insurance agent for an insurance company if the insured is in default will be returned to the insurance company because insurance agents only as intermediaries and authorized from the insurance company.